Expanding the Indications for Flow Diversion: Treatment of Posterior Circulation Aneurysms. (16th December 2019) - Adeeb, Nimer; Ogilvy, Christopher S; Griessenauer, Christoph J; Thomas, Ajith J
Abstract: Posterior circulation aneurysms are often associated with a higher risk of rupture and compressive symptoms compared to their anterior circulation counterpart. Due to high morbidity and mortality associated with microsurgical treatment of those aneurysms, endovascular therapy gained ascendance as the preferred method of treatment. Flow diversion has emerged as a promising treatment option for posterior circulation aneurysms with a higher occlusion rate compared to other endovascular techniques and a lower complication rate compared to microsurgery. While treatment of saccular and dissecting aneurysms is often associated with comparatively good outcomes, fusiform and dolichoectatic aneurysms should be carefully selected prior to treatment to avoid devastating thromboembolic complications. Occlusion of covered posterior circulation branches showed no correlation with ischemic complications, and appropriate antiplatelet regimen and switching Clopidogrel nonresponders to different antiplatelet agents were associated with lower complication rates following flow diversion of posterior circulation aneurysms.